Investigation of the structural, thermal and radiation shielding properties of (Er0.2Yb0.2Sm0.2La0.2Eu0.2)2Zr2O7 high entropy oxide reinforced tin matrix composite - Guler, Omer; Yilmaz, Demet; Kanca, M. Sait; Kok, Mediha; Guler, Seval Hale; Tasgin, Yahya (Elsevier Science Sa, 2026)
This study investigates the structural, thermal, and radiation shielding properties of (Er0.2Yb0.2Sm0.2La0.2Eu0.2)2Zr2O7 high entropy oxide (HEO) reinforced tin (Sn) matrix composites. In the first stage of the study, HEO powders were synthesized by grinding at 350 rpm for 30 h using a solid-state method with mechanical alloying assistance, and then calcining at 1100 degrees C for 8 h. In the second stage, composites were produced by mixing HEO-reinforced Sn matrix materials containing 1%, 5%, and 10% reinforcement, pelleting them under 200 MPa pressure, and then sintering them at 300 degrees C for 3 h. In the first stage of the study, (Er0.2Yb0.2Sm0.2La0.2Eu0.2)2Zr2O7 HEO powders were synthesized using a mechanical alloying-assisted solid-state route. In the second stage, HEO-reinforced Sn matrix composites containing 1 wt%, 5 wt%, and 10 wt% reinforcement were produced. The phase formation and crystallographic structure of the synthesized powders and composites were characterized using X-ray diffraction. Thermal behavior and phase stability were investigated by differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). The thermal analysis results revealed dehydration and structural stabilization processes at intermediate temperatures, while crystallization of the HEO phase was observed at elevated temperatures. In addition, oxidation behavior of the Sn matrix composites was evaluated, showing that the presence of HEO particles significantly suppresses mass gain during hightemperature oxidation, indicating improved thermal stability. Finally, the radiation shielding performance of the samples was experimentally evaluated within the photon energy range of 59.54-609.2 key using Am-241, Ba-133, and Ra-226 radioactive sources together with a Ultra-Low Energy Germanium (ULEGe) detector. The results demonstrate that the incorporation of HEO particles leads to minor, energy-dependent variations in the radiation attenuation capability of the tin matrix, influenced by the presence of high atomic number rare-earth elements and modified microstructural characteristics. The gamma radiation protection coefficient (RPC) values indicate strong attenuation in the low photon energy region, decreasing to approximately 16-19% at 609.3 key. Moreover, the measured neutron equivalent dose rates increase from 0.054 & micro;Sv/h for pure Sn to 0.285 & micro;Sv/h for the Sn-10%HEO composite, indicating that HEO incorporation modifies the neutron interaction behavior of the Sn matrix composites.
Keywords: High Entropy Oxide; Rare Earth; Composite; Radiation Shielding; Fast And Thermal Neutron